Conditions for a contribution by the Structural Funds to real convergence of the Recently Acceded Member States - Michael H. Stierle (European Regional Science Association (ERSA), 2005)
The recent EU enlargement poses immense challenges for EU regional policy in terms of increased necessity of priority setting and achieving allocative efficiency. In this context, the focus of this paper will be whether – or more precisely under which conditions – EU structural funds can be effective in making a significant contribution to real convergence in Europe. Based on theoretical insights and experiences in the incumbent Member States, conclusions will be drawn (though not exclusively) for the new Member States. In view of the very limited budgetary means of EU cohesion policy, representing less than 0.5 per cent of the EU-15 GDP, the following conditions will be identified as being important for maximising the impact: First, sound and supportive national policies, including macroeconomic policies, national regional policies and good governance, are an essential precondition for the achievement of a real impact. Second, the scarce financial means must be concentrated spatially, i.e. on the poorest Member States and regions and particularly in these countries they must be focused on national growth and growth poles rather than on equalising living conditions across the country and (more) dispersion of economic activity. Third, the strategic design of Structural Funds programmes must allow for a concentration on those types of expenditures most likely to lead to growth and employment. Fourth, ways have to be found to achieve the most effective use of EU Structural Funds. Before these conditions for maximising the impact of Structural Funds are described, empirical evidence and methods for assessing their contribution to real convergence in Europe will be discussed.
Keywords: 330